Describe The Translation. Y=(x−6)2+7 → Y=(x−1)2+3 A. T B. T C. T D. T

Describe The Translation. Y=(x−6)2+7 → Y=(x−1)2+3 A. T B. T C. T D. T

Transcribed Text:

Question: Describe the translation. y=(x-6)2+7 + y=(x-1)2+3 A. T<-5,-4> …
Describe the translation. y=(x-6)2+7 → y=(x-1)2+3
• A.T<-5,-4> • B. T<5,-4> • C. T<5,4> • D.T<-5,4>
Expert Answer
Anonymous answered this 2,782 answers
Was this answer helpful?
Was this answer helpful? B
i po
ya (x-6)2 +7 y = (x-6 + 5)2+7-4
It is shifted 5
y = (x-1)2 + 3
– y = (x-1)2 + 3 units to left and 4
units
down.
:
A
T<-5,-4>
(6, 7)
(1,3) 5
+
rn y=(x – 6)2 +7
y= (x – 1)2 + 3

Leave a Reply

Your email address will not be published. Required fields are marked *